State formation in Palestine : viability and governance during a social transformation - Amundsen, Inge; Giacaman, George; Khan, Mushtaq H. (Mushtaq Husain), 1961- (Political economy of the Middle East and North Africa ;, 2004)
This book examines key questions, and challenges the widely prevalent view that the Palestinian Authority collapsed because of its internal governance failures, its lack of commitment to democracy, and corruption.